DISTRIBUSI MAKROZOOBENTHOS DI PERAIRAN AEK MANIS KABUPATEN SIBOLGA SUMATERA UTARA - Irvina Nurrachmi; Zulkifli '; Esra Waty (Berkala Perikanan Terubuk, 2010)
This research was conducted in May 2009 in between District AekManis waters Sibolga North Sumatera in order to determine the correlationsediment organic material content and makrozoobenthos abundance.Determinantion of the research station was randomly composed of 4 station and 5sampling point where each point sampling distance of 200 meters wich werebased on the initial sampling paoint. Makrozoobenthos encountered and thestudy area there 26 genera of 3 classses, namely class gastropoda, bivalve.Polychaeta. Individuals from the class of individuals who gastropoda us mostoften found. On the whole it can be seen that the relation between sediment organicmaterial content and makrozoobenthos abudance show a positive correlation, thehighercontent of organic material wiil lead to the higher of the makrozoobenthosabundance.